Legal Regulation of Certain Grounds for Restricting Access to Environmental Information in the RA - Geghamyan , O. (Bulletin of Yerevan University C: Jurisprudence, 2017)
The modern era of information technologies and access to information is increasingly characterized by unprece- 76 dented level of transparency and public awareness with respect to decision making process on environmental matters. Nevertheless, access to information still remains one of strictly regulated areas and not all the information is readily available or randomly accessible to public upon demand. Access to data remains under governmental regulation, the reason being to protect privacy and interests of others who may suffer from such data sharing. Individual states and the international community have committed to regulate polices leading to creation of regulations restricting data sharing and access to protected information. This is equally true regarding environmental data and information. The present article is devoted to analysis of legal grounds for imposing restrictions on accessing environmental information in the context of applicable international legal framework. In particular, the relevant provisions of pertaining legislative acts of Armenia are discussed along with practical ramifications of their application. Special emphasize is made on data and information that shall be published anyway and no restriction is allowed based on the content of such information and international practices.